Task-Based Learning Used in Teaching Speaking at Senior High School - Faisal Anam; Siti Maria Ulfa; Moh. Hafidz (Penerbit STKIP PGRI Bangkalan, 2021)
The study aims to describe the implementation of task based learning in teaching speaking and studentsâ€™ responses toward the use of task based learning to teaching speaking in Senior High School. The research design of the study was descriptive qualitative. It involved a video from YouTube that relate with the title of the study. The title of the video is Implementasi Kurikulum 2013 Saintifik - Bahasa Inggris SMA/MAâ€ ( Implementation of the 2013 Scientific Curriculum - English Subject of Senior High School/MAâ€ ) in the YouTube channel â€œDunia Belajar 86â€. From the video that had been observed by the researcher, it can be concluded that Task-Based Learning was highly influential in teaching speaking skills as it could be seen from studentsâ€™ responses and enthusiasm in participating in the learning activities. Further, the teacher provided a lot of stimulation in the form of media and questions that made the students feel more interested in the subject being taught.